Enoyl acyl carrier protein reductase inhibitors: an updated patent review (2011 - 2015) - Zitko, Jan; Doležal, Martin (Expert opinion on therapeutic patents, 2016)
INTRODUCTION: Enoyl-(acyl-carrier-protein) reductase (ENR) is a limiting step enzyme in the Fatty Acid Synthase II system. In mammals, there is no homologue to ENR, which makes it an optimal candidate target for selective anti-infective drugs. Up-to-date, only two ENR inhibitors are used in clinical practice. AREA COVERED: This review is a survey on important patents on low molecular weight compounds with ENR inhibiting activity published in 2011-2015. Common patent databases (SciFinder, esp@cenet, WIPO) were used to locate patent applications on the proposed topic and in the timespan of 2011-2015. EXPERT OPINION: In 2011-2015, we have observed patents in previously known structural groups of diphenyl ethers and acrylamides as well as new structural classes, often identified by high-throughput screening campaigns. The spectrum of activity of applied derivatives covers significant bacteria, mycobacteria, and apicomplexan parasites (Plasmodia and Toxoplasma). Good news from research of ENR inhibitors: a) four selective anti-staphylococcal compounds applied in 2011-2015 or earlier were pushed to Phase I or Phase II clinical trials and some of them proved safety and tolerability after peroral and/or intravenous administration; b) big pharma companies have renewed their interest in the development of new anti-infective compounds against resistant strains of clinical relevance.
Keywords: High-Throughput Screening Assays; antiinfekční látky; patenty jako téma; enoyl-acyl-carrier-protein reductase; FabI; Acrylamide; antibiotická rezistence; Anti-Infective Agents; antibacterial; rychlé screeningové testy; zvířata; Humans; racionální návrh léčiv; MRSA; Patents as Topic; enoyl-ACP-reduktasa (NADH); InhA; triclosan; Enoyl-(Acyl-Carrier-Protein) Reductase (NADH); Drug Resistance, Microbial; Drug Design; antimycobacterial; Enzyme Inhibitors; lidé; inhibitory enzymů; Animals